On the Importance of Sales for Aggregate Price Flexibility - Oleksiy Kryvtsov; Nicolas Vincent (Bank of Canada, 2014)
Macroeconomists have traditionally ignored the behavior of temporary price markdowns ("sales") by retailers. Although sales are common in the micro price data, they are assumed to be unrelated to macroeconomic phenomena and generally filtered out. We challenge this view. First, using the 1996 - 2012 data set of the U.K. CPI monthly price quotes, we document a roughly twofold increase in the frequency of sales during the Great Recession. We also present evidence of countercyclical sales in the United States. Second, we build a New Keynesian macroeconomic model in which temporary sales arise as a pricing mechanism that allows retailers to price discriminate across consumers with different opportunity costs of time. In line with our empirical evidence, the model predicts that firms react to macroeconomic shocks by varying the frequency of sales. In response to a monetary contraction, firms facing costs of decreasing regular prices post more sales, and households spend more time looking for sales. The resulting fall in the aggregate price level can be significantly larger than if sales were ignored. When the model is calibrated to match the behavior of sales in the data, it implies that the sales margin leads to a much smaller response of real consumption to monetary shocks.
Keywords: E31; E32; E52; L11; L25; L81; M31; 330; Business fluctuations and cycles; Economic models; Inflation and prices; Market structure and pricing; Transmission of monetary policy